MEMBUAT PETA PIKIRAN PADA KEGIATAN PRABACA UNTUK MENGIDENTIFIKASI IDE POKOK DAN MENYIMPULKAN ISI TEKS BERITA MELALUI COLLABORATIVE ACTION RESEARCH - Sumarwati Sumarwati; Siti Martabatul (Universitas Sebelas Maret, 2019)
One of the obstacles in developing reading skills in students is that they are not trained in reading activities for specific purposes. Therefore, students read by giving equal attention to all parts of the reading. Thi study aims to improve the reading ability through thue use of mind mapping. This study was an classroom action research and conducted in three cycles. The participants were students class 8D and Indonesian Language teacher of SMP Negeri 8 Surakarta. The result showed that there was an improvement in the percentace of formulating the mind map, reading activity and ability. The effective learning procedure was as follows. The students surveyed the text, identified the main idea of the text with questions word 5W + 1 H, formulated mind map, memorized the main idea of mind map, read the text intensively that they could use their maps as a review of information gained, stated the conclusion about ideas in the mind map, and answered the questions (take a test. The conclusion of this study is that the main ideas identified in the pre-reading activities to be developed into a mind band, not only allows the reading activities with a specific purpose, but also helps students to focus attention on the parts of the text.